2002
DOI: 10.1042/bj3630581
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic degradation of plasma arginine using arginine deiminase inhibits nitric oxide production and protects mice from the lethal effects of tumour necrosis factor α and endotoxin

Abstract: Septic shock is mediated in part by nitric oxide (NO) and tumour necrosis factor α (TNFα). NO is synthesized primarily from extracellular arginine. We tested the ability of an arginine-degrading enzyme to inhibit NO production in mice and to protect mice from the hypotension and lethality that occur after the administration of TNFα or endotoxin. Treatment of BALB/c mice with arginine deiminase (ADI) formulated with succinimidyl succinimide polyethylene glycol of Mr 20000 (ADI-SS PEG20000) eliminated all measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 40 publications
(68 reference statements)
2
14
0
Order By: Relevance
“…These results suggest that ADI treatment did not directly suppress the expression of VEGF, but clearly reduced angiogenic activity in tumor tissue. ADI inhibited the production of nitric oxide (NO) by nitric oxide synthase (NOS) through the modulation of extracellular level of arginine,5, 32, 33 and NO plays a role in angiogenesis because it could modulate the activity of vascular endothelial growth factor, basic fibroblast growth factor and matrix metalloproteinases 34, 35. Arginine deprivation by ADI could also alter the levels of polyamines, proline and glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that ADI treatment did not directly suppress the expression of VEGF, but clearly reduced angiogenic activity in tumor tissue. ADI inhibited the production of nitric oxide (NO) by nitric oxide synthase (NOS) through the modulation of extracellular level of arginine,5, 32, 33 and NO plays a role in angiogenesis because it could modulate the activity of vascular endothelial growth factor, basic fibroblast growth factor and matrix metalloproteinases 34, 35. Arginine deprivation by ADI could also alter the levels of polyamines, proline and glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…ADI from Mycoplasma arginini has a powerful anticancer potency toward various tumors . The dependency of tumor cells on blood l ‐arginine for rapid proliferation was reported more than 50 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…ADI was well characterized from Bacillus cereus , Pseudomonas sp, Leuconostoc oenos , Lactobacillus sp, Listeria monocytogenes , Clostridium perfringens , and Mycoplasma sp . ADI was absolutely absent in mammals . However, few studies on fungal ADI have been reported, despite its hypothesized affordable biochemical properties compared with bacterial ADI …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant arginine deiminase (rADI) with the modification of polyethylene glycol was recently developed as an antitumor drug for patients with hepatocellular carcinoma and melanoma (Shen and Shen, 2006). In addition, rADI was shown to have beneficial effects on the maintenance of blood pressure in septic animals because of suppression of iNOS‐induced NO production (Thomas et al, 2002). However, the effects of rADI on NO‐induced neuronal diseases remain unknown.…”
mentioning
confidence: 99%